(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Catering services is a fast-growing industry severely affected by the COVID-19 pandemic. The banquet and catering businesses were shut down, causing profit and employment loss affecting many people, communities, and businesses worldwide. Adjusting to the new normal has been challenging for the industry, with companies temporarily closed due to lockdowns and restrictions. Before conducting an event, the capacity of the venue must be checked due to different health protocols to follow, and the number of guests is limited. Researchers conducted a study to determine the challenges encountered in banquet and catering services during the pandemic that affect employees and employers. The researchers used a descriptive technique to identify the challenges in banquet and catering services during the pandemic. They gathered data using a survey questionnaire administered via Google Forms to fifty (50) employers and employees from the banquet and catering services in Brgy. Commonwealth, Quezon City as their target respondents. According to the online survey’s findings, the majority of respondents are female, between the ages of 18 and 22, and single. The majority of their work position is being a service personnel. 66% of the total population prefer to have their preparations two days before the event. The respondents admitted that they are greatly affected by salary, schedule, location, transportation, and health. They faced many challenges that burdened them while working in the industry, particularly having social distancing while in an event. In contrast, every business had to adjust, which may be more difficult for some than others, with a percentage of 90. Based on the gathered data and conclusions drawn, the researchers evaluated and determined the challenges different banquet and catering services encountered during the pandemic. This study focused on gathering ways to overcome the challenges that the banquet and catering services help the industry to grow. The gathered data will provide critical factors in commitment to the economic success of the catering industry amidst the pandemic.